The Road to Net-Zero Emission in Indonesia: Legal Loopholes in National Carbon Tax Scheme - Indria Wahyuni; Rahadyan Fajar Harris; Emanuel Sujatmoko (Media Iuris, 2023)
Indonesia is committed to accelerating the achievement of Net-Zero Emissions by 2060. The Carbon tax is a new instrument that it believes could encourage the achievement of carbon neutrality. Through the Harmonisation of Tax Regulations Act, the Government regulated several carbon tax provisions, which were initially going to be implemented on April 1, 2022, and then postponed to July 1, 2022. Unfortunately, the carbon tax implementation has been delayed until an undetermined time. Implementing legal interpretation, this research comprehensively analyses carbon tax provisions in the Harmonisation of Tax Regulations Act. The research will examine the ability of current carbon tax arrangements to accelerate the achievement of Zero Emissions. This work uses normative juridical methods with a conceptual and statutory approach to provide recommendations. The results show that the carbon tax arrangement does not contain substantial clarity, and various implementing regulations are needed. Article 13 of the Harmonisation of Tax Regulation Act contains vague norms that need to be elaborated. The paper recommends the urgency of legislative review mechanism for the Harmonisation of Tax Regulation Act, especially Article 13, and the need to harmonise it with related laws.